WHAT INFORMS CHOICE IN OBSTETRIC TRANSFUSION DECISION-MAKING?. (February 2015) - Mayson, Eleni; Ford, Jane
Abstract : Background: Most obstetric blood transfusions occur in the setting of postpartum haemorrhage (PPH). Blood is precious, not risk-free and some women can be safely managed without a blood transfusion. Aim: To identify factors associated with variation in obstetric transfusion rates, and to explore postpartum transfusion triggers across institutions with a range of transfusion rates. Methods: A qualitative research study using semi-structured interview was conducted. Nine maternity units were chosen to cover a range of clinical settings and obstetric transfusion rates. Interviews were conducted in person with the key decision-makers in the maternity blood transfusion process: haematologists, obstetricians, midwives, midwifery unit managers and clinical midwifery educators. Interviews were transcribed, coded, and NVivo qualitative software was used to develop themes. Results: 126 interviews were conducted: 61 clinician interviews were coded in detail and the rest provided contextual data. High transfusing hospitals were more likely to be rural, treat lower risk women, have lower staff numbers and skill-mix, have smaller blood inventories with less blood product regulation, and have lower tolerance for maternal anaemia. Discussion: This study identifies hospital-based, clinician-based and patient-based factors influencing obstetric blood transfusion practice. Different factors predominate in each institution, and identifying potentially modifiable factors may provide a focus for practice improvement.